Development of a centrifuge for high speed centrifugal extraction of moisture from macerated water hyacinth. - Calilung, Edwin J.
Rapid mechanical dewatering of fibrous vegetative materials like water hyacinth requires separation of the process into two steps of maceration (cell breakage) and moisture extraction, to allow individual optimization for speed and efficiency. To fulfill the second step, centrifugal moisture extraction was explored. Centrifugal moisture extraction characteristics were determined using a fabricated batch loading centrifuge to determine its potential for rapid moisture extraction. A continuous loading conical centrifuge was designed, fabricated and tested for continuous high capacity moisture extraction from macerated of water hyacinth.